Fostering human–robot cooperative architectures for search and rescue missions in urban fires. (March 2021) - Couceiro, Micael S; Portugal, David; Rocha, Rui P; Araújo, André
Urban fires are probably the most frequent catastrophic incidents in urban areas, requiring a prompt response due to life endangerment in highly populated zones and the high risk of fire propagation to buildings and parked cars in the vicinity. Robot assistance has been identified as a valuable resource for such urban search and rescue (USAR) scenarios by taking advantage of robots' expendability. However, it is still unclear or not quantified how advantageous such human–robot cooperation can be to the final outcome of firefighting operations and other USAR missions. This article reports research in this context by modeling key features of a firefighting mission in response to an urban fire in a large basement garage. Besides building a behavioral model of human firefighting teams based on interviews with a Portuguese Fire Department, and assessing their performance under different circumstances, this work studies the addition of robotic teams in cooperation with human firefighters to overcome communication issues and improve situation awareness. The results obtained highlight the importance of such human–robot partnership for a more effective response to an urban fire and mitigation of life endangerment of first responders and victims.